Empowering Elementary Students Through Metacognitive-Based Digital Pop-Up Books: A Study on Independence and Learning Mindset - Wulandari, Katarina Ni Made Sonia Putri (Journal of Education Technology, 2024)
The lack of adequate IPAS learning media in elementary schools has negatively impacted students’ independence and learning mindset during the learning process. This study aims to analyze the effectiveness of a metacognitive-based digital Pop-Up Book in enhancing the independence and learning mindset of fourth-grade elementary students. This developmental research utilized the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The subjects of the study were 13 fourth-grade students. Data collection methods and instruments involved questionnaires. The findings indicate that the developed product demonstrates high validity and practicality, as evidenced by a student response score averaging 90%, categorized as excellent. The results of the correlated t-test showed a significance value (2-tailed) of 0.001 or p < 0.05. Therefore, it can be concluded that the metacognitive-based digital Pop-Up Book on the topic of photosynthesis is effective in improving students' learning independence and mindset. Based on the findings, recommendations include enhancing the quality of learning media by deeply integrating technology, designing more interactive and child-friendly features, and developing learning activities that encourage greater student independence while fostering their learning mindset.